2010
DOI: 10.4238/vol9-4gmr883
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic study of single-nucleotide polymorphism within candidate genes associated with type 2 diabetes in

Abstract: ABSTRACT. A population-based study was undertaken to evaluate linkage between single-nucleotide polymorphisms known as risk factors and type 2 diabetes in an Indian population. The study population was comprised of 40 normal glucose-tolerant individuals (21 males and 19 females) and 40 type 2 diabetes patients (21 males and 19 females). The genes and their corresponding single-nucleotide polymorphisms that we screened were VDR (rs 731236 and rs 1544410), IL-6 (rs 1800795), TCF7L2 (rs 7903146) and TNF-α (rs 180… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 31 publications
6
17
0
Order By: Relevance
“…We found that in a Chinese Han population, there were alleles B and b at the BsmI site of VDR gene, and the bb genotype accounted for 85%, Bb for 14%, and BB for 1% in the control individuals, consistent with the results found in HapMap of Han Chinese in Beijing (CHB) (bb 87.5%, Bb12.2%) and Zhang et al (Zhang et al, 2005). In the patients with type 2 diabetes, the BB + Bb genotype and allele B frequency were significantly higher than in control individuals, which was consistent with reports by Oh (Oh and Barrett-Connor, 2002), Shi (Shi et al, 2007) and Mukhopadhyaya (Mukhopadhyaya et al, 2010), indicating a correlation between BsmI polymorphism and type 2 diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…We found that in a Chinese Han population, there were alleles B and b at the BsmI site of VDR gene, and the bb genotype accounted for 85%, Bb for 14%, and BB for 1% in the control individuals, consistent with the results found in HapMap of Han Chinese in Beijing (CHB) (bb 87.5%, Bb12.2%) and Zhang et al (Zhang et al, 2005). In the patients with type 2 diabetes, the BB + Bb genotype and allele B frequency were significantly higher than in control individuals, which was consistent with reports by Oh (Oh and Barrett-Connor, 2002), Shi (Shi et al, 2007) and Mukhopadhyaya (Mukhopadhyaya et al, 2010), indicating a correlation between BsmI polymorphism and type 2 diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…VDR polymorphism (rs731236 T/C) analysis in a Vietnam study has shown that C allele (author named as t allele) at position 352 was resistant to DSS (p trend analysis) [39]. This correlates with a recent report that VDR T allele was a risk factor of type 2 diabetes with insulin secretion capacity [40]. …”
Section: Host Genetic Factors Involved In the Clinical Course Of Dmentioning
confidence: 55%
“…Considering the high prevalence of vitamin D deficiency in Iranian subjects either with or without diabetes [17,19] and assuming the same prevalence of "non-responders" among the whole population, a huge number of people may not benefit from intake of the usually recommended amount of vitamin D. This individual variability may be, at least in part, explained by vitamin D receptor (VDR) polymorphisms. A significant association between VDR variants and susceptibility to several diseases including cancer [20,21], ulcerative colitis [22], metabolic syndrome [23] and both types of diabetes [24,25] has already been reported. The upcoming results from our study group will soon address the role of VDR genotypes on the variation of outcomes after improvement of vitamin D status in subjects with T2D [12].…”
Section: Discussionmentioning
confidence: 99%